Metodología para el Muestreo y Manipulación de muestras de Aguas y Aguas Residuales en un Labmovil. - Díaz Aguirre, Susana; Mayari, Rogelio; Del Carmen Espinosa, Maria; Hernández Díaz, Rebeca (Revista CENIC Ciencias Quimicas)
The University of Pinar del Río has a Mobile Laboratory that offers a specialized service in taking, conservation and transportation of samples of waters and wastewaters. As well as, carries out "in situ" physical and chemical analysis of their quality. The present work has as objective to establish a methodology for the sampling and manipulation (conservation and transportation) of the samples of waters and wastewaters assuring the integrity of the sample from its taking until the emission of the report, for that which, it is necessary to make a relationship of the possession process and manipulation of the sample from the moment in that it is taken until to its analysis and its elimination. This process is denominated chain of vigilance. The methodology for sampling consists in: planning and programming of the sampling (process of implementation of the administration system, sampling plan); preparation and assurance of the sampling (assurance system, administrative process, equipment preparation, assurance of the transportation); taking of samples-control and vigilance (field registration, sampling, field measurements, filled and preservation, labeled, sealed, conservation, transportation, registration and sending to the laboratory); corrective action; final report (database, statistical processing, elaboration of the report); conformity. The Mobile Laboratory assures an immediate diagnostic of the following indicators: pH, Electrical Conductivity, Dissolved Oxygen, Temperature, Total Dissolved Solids and Salinity, operating a Quality System according with the Standard NC-ISO/IEC 17025: 2004. The use of this norm will facilitate the cooperation between laboratories and other organisms, with the objective of contributing to the exchange of information and of experience, and to the harmonization of the norms and procedures. Also, the general actions of the administration guaranteed the full satisfaction of the demands of the clients, as is demonstrated in the present work, combining high levels of precision and accuracy with short times in the delivery of results and decrease of the costs in the studies carried out, that is efficiency and quality in the services.